2015
DOI: 10.1016/j.engfracmech.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent brittle-to-ductile transition in GaAs nano-rods

Abstract: a b s t r a c tGaAs is brittle at room temperature at the macro-scale; however, ductility emerges when its characteristic dimension reduces to the nano-scale. Using molecular dynamics simulations, we reveal that there is a brittle-to-ductile transition in GaAs nano-rods due to the competition between generation of cracks and initiation of dislocations. Such a competition is sensitive to aspect ratios of nano-rods. These results well explain experimentally observed ductility of GaAs nano-rods and have important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Secondly, as shown in the partial cross-sectional structure in Figure 9c, nanostructures that are under high ion-dose appear as 1/6<112> dislocation types, whose motion ensures plastic deformation. It is also demonstrated in the study of Wang et al [31] In terms of Young's modulus, Figure 9d shows that the mechanical parameters usually decrease with increasing dose, reaching saturation at doses greater than 4 × 10 14 ions/cm 2 at 5 keV energy. Point defects and small clusters induce changes in the mechanical properties of GaAs NWs at low ion doses, while a crystalline to amorphous (c-a) transition occurs at high doses, saturating the mechanical properties.…”
Section: Tensile Deformation Of Irradiated Gaas Nwssupporting
confidence: 64%
See 2 more Smart Citations
“…Secondly, as shown in the partial cross-sectional structure in Figure 9c, nanostructures that are under high ion-dose appear as 1/6<112> dislocation types, whose motion ensures plastic deformation. It is also demonstrated in the study of Wang et al [31] In terms of Young's modulus, Figure 9d shows that the mechanical parameters usually decrease with increasing dose, reaching saturation at doses greater than 4 × 10 14 ions/cm 2 at 5 keV energy. Point defects and small clusters induce changes in the mechanical properties of GaAs NWs at low ion doses, while a crystalline to amorphous (c-a) transition occurs at high doses, saturating the mechanical properties.…”
Section: Tensile Deformation Of Irradiated Gaas Nwssupporting
confidence: 64%
“…For the simulation part of ion implantation, we have adopted the hybrid potential by Albe et al [36] and Gao et al [10] In terms of the tensile deformation simulations, we use the Vashishta potential function which is very close to the experimental value in describing the elastic constants of the GaAs crystal [37]. This potential function has been used several times to simulate the stretching and compression of GaAs NWs, showing a series of mechanical characteristics such as size effect, brittle to ductile transition, and self-healing phenomena, all of which have been demonstrated in the experiment [30,31]. The parameters related to the Vashishta potential are taken from Ref.…”
Section: Interatomic Potentialsmentioning
confidence: 92%
See 1 more Smart Citation
“…Wang et al [15] revealed that there is a brittle-to-ductile transition in GaAs nano-rods because of the competition between the generation of cracks and initiation of dislocations.…”
Section: Introductionmentioning
confidence: 99%